2023
DOI: 10.1096/fj.202201564r
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the detrimental developmental impact of early fetal alcohol exposure using a maternal methyl donor‐enriched diet

Abstract: Fetal alcohol exposure at any stage of pregnancy can lead to fetal alcohol spectrum disorder (FASD), a group of life-long conditions characterized by congenital malformations, as well as cognitive, behavioral, and emotional impairments. The teratogenic effects of alcohol have long been publicized; yet fetal alcohol exposure is one of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 151 publications
(362 reference statements)
0
17
0
Order By: Relevance
“…Prenatal alcohol exposure was previously shown to alter embryonic development in different contexts, by inducing fetal growth restriction or growth delay (14, 15). With our model, we found that the impact on growth and related pathways was more pronounced in male ethanol-exposed placentas, consistent with the observed male-specific changes in genes regulating growth, cytoskeletal organization, placental development, and vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal alcohol exposure was previously shown to alter embryonic development in different contexts, by inducing fetal growth restriction or growth delay (14, 15). With our model, we found that the impact on growth and related pathways was more pronounced in male ethanol-exposed placentas, consistent with the observed male-specific changes in genes regulating growth, cytoskeletal organization, placental development, and vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant females were separated from the males and housed together ( n= 2–3) in a 12-h light/dark cycle with unrestricted access to food and water. Like in our previously published preimplantation binge-like PAE model (14, 15), pregnant females were subcutaneously injected with two doses of either 2.5 g/kg of 50% ethanol or an equivalent volume of saline at 2-h intervals on E2.5 (the 8-cell stage), then housed under similar conditions with limited handling during gestation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hallmark features of FASD include physical anomalies, cognitive deficits, and behavioral issues [19]. Physical characteristics may include facial abnormalities, growth deficiencies, and organ malformations [20]. Cognitive impairments often encompass difficulties in learning, memory, attention, and problemsolving skills [21].…”
Section: Fetal Alcohol Spectrum Disorders (Fasd)mentioning
confidence: 99%
“…Preclinical studies indicated a lower risk of neural tube defects, prostatitis, and autisticlike behaviors after folate supplementation during pregnancy (Budni et al, 2013;Silva et al, 2017). These effects may extend to mitigating the negative consequences of PEE (Breton-Larrivée et al, 2023). Sogut et al (2017) reported that folic acid ameliorated PEE-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%